ANALISIS HUKUM PERUBAHAN SKEMA MANDATORY SPENDING KESEHATAN: UPAYA MEWUJUDKAN EFISIENSI ANGGARAN BERBASIS KINERJA DALAM PEMBANGUNAN NASIONAL - Yudhi Hertanto (CV. Lafadz Jaya, 2026)
The transformation of health regulations in Indonesia through Law Number 17 of 2023 has fundamentally overhauled the national health financing architecture. The most crucial change is the elimination of the mandatory spending scheme, previously set at 5% of the national budget (APBN) and 10% of the regional budget (APBD). This study aims to analyze the legal and philosophical implications of the transition to performance-based budgeting within the national development legal framework. Using normative legal research methods, the study found that this policy constitutes a form of social engineering to address inefficient regional fund absorption. However, the elimination of this minimum threshold poses the risk of legal uncertainty regarding the fulfillment of the human right to health if not accompanied by rigid performance indicators. An optimization strategy through Minimum Service Standards (SPM) and the Health Sector Master Plan (RIBK) is an absolute requirement to ensure inclusive fiscal sustainability in health